Pure Laparoscopic Left Hepatectomy for Regrowth of Mucinous Cystic Neoplasm of the Liver after Laparoscopic Deroofing - Hideki Kumagai; Akira Umemura; Hiroyuki Nitta; Hirokatsu Katagiri; Shoji Kanno; Daiki Takeda; Satoshi Amano; Koji Kikuchi; Kiyoharu Takashimizu; Masao Nishiya; Noriyuki Uesugi; Tamotsu Sugai; et al. (Case Reports in Surgery)
Background. Hepatic cystic lesions are common entities, most of which are simple hepatic cysts (SHCs). Mucinous cystic neoplasm of the liver (MCN-L) is a rare tumor characterized by ovarian-like stroma and accounts for <5% of all hepatic cysts. Distinguishing between SHCs and MCN-L is challenging because of the similarity in their imaging findings. Herein, we report a rare regrowth case of MCN-L after laparoscopic deroofing, treated with pure laparoscopic left hepatectomy. Case Presentation. A 63-year-old woman with a large hepatic cystic lesion and abdominal pain was referred to our hospital for surgical treatment. Computed tomography (CT) showed cystic lesions with septations arising from macrolobulations in the left medial segment. She underwent laparoscopic deroofing based on the diagnosis of SHCs; however, the final histopathological diagnosis was MCN-L. She chose observational follow-up, and MCN-L regrowth was detected on follow-up CT 6 months after the laparoscopic deroofing. We performed pure laparoscopic left hepatectomy for complete resection of the MCN-L. She had an uneventful postoperative course and no recurrence at the 5-year follow-up after the radical resection of the MCN-L. Conclusion. MCN-L is a rare entity, and accurate diagnosis with imaging modalities is greatly challenging. Laparoscopic hepatectomy for MCN-L should be considered as a strong alternative to secure safety and curability.